Urban Congestion Charging: Theory, Practice and Environmental Consequences - Georgina Santos; David Newbery (Center for Economic Studies and ifo Institute (CESifo), 2001)
The theory of road pricing developed for single links suggests time andlocation varying charges equal to the marginal congestion cost at the efficientlevel of traffic. The second-best network counterpart is derived, but would beinfeasible to implement. Cordon tolls are feasible, and their optimal levelcomputed for eight towns. A cost-benefit study showed that with a suitablechoice of location, all schemes were socially profitable, though with widevariations across towns. The environmental benefits of cordon tolls aremeasured and shown to correlate with optimal congestion tolls, but to bemodest in size and not to affect the optimal toll.
Keywords: 330; road traffic congestion; road pricing; congestion charging; cordontolls; environmental taxes.